Tunable wave-absorbing metamaterial and preparation method and application thereof

By preparing a magnetic slurry containing polymer matrix, wave absorber and magnetic particles, and using 3D direct-write printing technology to build a tunable wave absorbing metamaterial, the problems of limited absorption frequency band, complex process and lack of flexibility in the prior art are solved, and flexible, precise and stepless regulation of electromagnetic wave absorption is achieved.

CN119651193AActive Publication Date: 2025-03-18ZHEJIANG UNIV OF TECH +1

Patent Information

Application Number
CN202411695435.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-18
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing preparation methods of electromagnetic wave absorption materials have shortcomings in electromagnetic wave absorption regulation due to single material composition, limited absorption frequency band, complex process, and lack of flexibility and real-time in electromagnetic wave absorption regulation.

Method used

By preparing a magnetic slurry containing a polymer matrix, a wave absorber and magnetic particles, and using 3D direct writing printing technology to build a tunable wave absorbing metamaterial, the transformation of pore structure under magnetic field drive can achieve stepless regulation of different frequency bands.

Benefits of technology

It realizes flexible, precise and stepless regulation of electromagnetic wave absorption, simplifies the preparation process, reduces costs, and improves the controllability of the microstructure and performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651193A_ABST
    Figure CN119651193A_ABST
Patent Text Reader

Abstract

The invention discloses a tunable wave-absorbing metamaterial and a preparation method and application thereof, and belongs to the technical field of wave-absorbing materials.The method comprises the steps that 1, slurry containing a high-molecular polymer matrix, a wave-absorbing agent and magnetic particles is prepared and magnetized, and magnetic slurry is obtained; (2) designing a porous target metamaterial structure to be printed, and performing magnetic programming on the target metamaterial, so that the pore structure of the target metamaterial is changed and adjustable under the action of a magnetic field; and (3) putting the magnetic slurry into slurry direct-writing 3D printing equipment, printing according to the designed mode, and carrying out thermocuring after printing is completed, so as to prepare the tunable wave-absorbing metamaterial of which the pore structure can be converted under the driving of a magnetic field. The method disclosed by the invention is simple and efficient in steps, overcomes the defects in the aspect of regulating and controlling the electromagnetic wave absorption performance of the existing wave-absorbing material, and has a wide application prospect in the fields of aerospace and communication equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of absorbing materials, and in particular to a tunable absorbing metamaterial and a preparation method and application thereof. Background Art

[0002] The efficient absorption and precise control of electromagnetic waves play an important role in many fields such as communications, electromagnetic compatibility, and national defense security. Nowadays, the popularity of electronic devices continues to increase, and the electromagnetic environment is becoming increasingly complex and changeable. The electromagnetic interference and radiation generated by some high-power electromagnetic radiation sources may affect the normal operation of equipment and human health. Electromagnetic wave absorbing materials can convert electromagnetic energy into other forms of energy to achieve electromagnetic wave attenuation. Therefore, the demand for high-performance electromagnetic wave absorbing materials and control methods is becoming increasingly urgent.

[0003] In the prior art, common methods for preparing electromagnetic wave absorbing materials usually have many problems. For example, some methods use a single material composition, resulting in a limited absorption frequency band, which is difficult to meet the needs of broadband absorption; some methods have complex process flows, requiring multiple steps and expensive equipment, which increases production costs and time costs. In terms of regulating electromagnetic wave absorption performance, existing technical means are often not flexible enough and it is difficult to achieve real-time and dynamic adjustment.

[0004] A Chinese patent document with publication number CN117335167A discloses a dual-band tunable broadband absorbing structure based on a periodic structure of a resistor film. The invention comprises a metal substrate and three absorbing structural layers arranged thereon to form an absorbing structural unit, and a plurality of absorbing structural units are arranged periodically. The absorbing structural layer comprises a dielectric layer, a substrate, and a resonant layer arranged on the surface of the substrate close to the dielectric layer. The resonant layer comprises an annular polygonal resistor film. The width and the length of the longest diagonal of the annular polygonal resistor film in each resonant layer from bottom to top decrease successively, and the surface resistance increases successively. The absorbing structure can achieve high-performance absorption in a dual-band ultra-wide frequency band, and the broadband absorption frequency point is precisely controllable.

[0005] A Chinese patent document with publication number CN116769300A discloses a tunable composite absorbing material based on a honeycomb structure and a preparation method thereof. The invention cross-links magnetic absorbing particles and a resin matrix to form a gel composite absorbing material; makes a mold cavity of the honeycomb structure; injects the gel composite absorbing material into the mold cavity of the honeycomb structure; utilizes a packaging process to composite the honeycomb structure with the gel composite absorbing material to obtain a tunable composite absorbing material based on the honeycomb structure; applies an excitation magnetic field to the tunable composite absorbing material based on the honeycomb structure, and forms an absorbing superstructure of the tunable composite absorbing material based on the honeycomb structure by regulating the magnetization state.

[0006] The above-mentioned absorbing materials / absorbing structures can have good electromagnetic wave absorption effects in specific frequency bands, or can ensure a certain material stability during the preparation process. However, there are also some problems. First, the selection of raw materials and the formulation of composite materials limit the range of the absorption band and cannot adapt to a variety of electromagnetic environments; secondly, the complex preparation process is not only inefficient, but also difficult to accurately control the microstructure and performance of the material. Furthermore, in terms of the regulation of electromagnetic wave absorption, there is a lack of flexibility and real-time performance, and the absorption characteristics cannot be quickly changed according to actual needs. Summary of the invention

[0007] The present invention provides a method for preparing a tunable absorbing metamaterial, which has simple and efficient process steps. The method effectively overcomes the deficiencies in the prior art in regulating the electromagnetic wave absorption performance of absorbing materials through a combination of process and raw materials, and has broad application prospects and practical value in the fields of anti-electromagnetic interference, aerospace or communication equipment.

[0008] The specific technical solutions adopted are as follows: A method for preparing a tunable wave-absorbing metamaterial comprises the following steps: (1) preparing a slurry comprising a polymer matrix, an absorber and magnetic particles, wherein the mass ratio of the polymer matrix, the absorber and the magnetic particles in the slurry is 20-30:1:20-40; and magnetizing the slurry to obtain a magnetic slurry; (2) Designing the porous target metamaterial structure to be printed, and performing magnetic programming design on the target metamaterial so that the pore structure transformation of the target metamaterial is adjustable under the action of a magnetic field; (3) placing the magnetic slurry of step (1) in a slurry direct writing 3D printing device, printing it according to the method designed in step (2), and thermally curing it after printing to prepare a tunable absorbing metamaterial whose pore structure can be transformed under the drive of a magnetic field.

[0009] The pore structure can be transformed under the drive of a magnetic field. Specifically, the tunable absorbing metamaterial is placed under a magnetic field (permanent magnet, coil, electromagnet). The absorbing metamaterial can change its internal pore structure as the size and direction of the magnetic field are regulated, thereby achieving stepless regulation of absorption of different frequency bands.

[0010] The method of the present invention is based on magnetic slurry with excellent performance. Through the precise design of the target metamaterial structure and accurate programming of the printing path, the accuracy and controllability of the preparation of the target metamaterial are ensured. In addition, by using advanced 3D direct writing printing technology, complex metamaterial structures can be easily constructed, further improving the absorption and regulation capabilities of electromagnetic waves.

[0011] The high molecular polymer matrix includes, but is not limited to, silicone rubber, polydimethylsiloxane (PDMS), polyurethane, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polycarbonate, polyamide (such as nylon), polyester (such as polyethylene terephthalate) and the like.

[0012] Preferably, when the polymer matrix is ​​silicone rubber or PDMS, the mass ratio of the polymer matrix, the absorber and the magnetic particles is 20-25:1:20-30; when the polymer matrix is ​​polyurethane or polyethylene, the mass ratio of the polymer matrix, the absorber and the magnetic particles is 25-30:1:25-40. In the above preferred case, the rheological properties of the slurry are better, which is beneficial to the absorbing performance of the absorbing metamaterial.

[0013] The absorber is selected from at least one of reduced graphene oxide, carbon nanotubes, carbonyl iron powder, manganese zinc ferrite, nickel zinc ferrite, silver nanoparticles, gold nanoparticles, polyaniline, polypyrrole, silicon carbide, titanium dioxide, hexagonal boron nitride, etc. In the slurry, the absorber not only acts as an absorbing material, but also as a thickener to improve the rheological properties of the slurry.

[0014] The magnetic particles are hard magnetic particles, which include at least one of neodymium iron boron powder, samarium cobalt alloy powder, barium ferrite powder, strontium ferrite powder, and aluminum nickel cobalt alloy powder; further, the average particle size of the hard magnetic particles is ≤30 μm.

[0015] Furthermore, the slurry also includes a curing co-catalyst of a high molecular polymer matrix, and the mass ratio of the high molecular polymer matrix to the co-catalyst is 1-3:1.

[0016] Preferably, the slurry is magnetized to saturation under a pulsed magnetic field or a permanent magnet, and the magnetization intensity is generally 2-4 T. It can be magnetized to saturation in an instant to obtain a magnetic slurry.

[0017] Specifically, the slurry direct writing 3D printing device includes a nozzle, a magnetic shielding cover is installed around the nozzle, and electromagnets are symmetrically arranged on the magnetic shielding cover around the nozzle. The direction of the magnetic field at the nozzle is changed by changing the current direction of the electromagnet, so that the extruded slurry is printed in a magnetic programming manner.

[0018] In the printing process, nozzles of different specifications and printing speeds can be selected according to different precision requirements. Preferably, the nozzle diameter is 210-620 μm and the printing speed is set to 3-15 mm / s. The thermal curing conditions depend on the polymer matrix. Generally speaking, the thermal curing conditions are 20-250°C and the time is 30min-10h.

[0019] The present invention also provides a tunable wave-absorbing metamaterial prepared by the preparation method of the tunable wave-absorbing metamaterial.

[0020] The tunable absorbing metamaterial has different shrinkage degrees of pore structure as the magnetic field strength changes. Its absorbing performance is flexible and variable. The absorbing frequency and absorption rate can be precisely controlled with the help of magnetic field according to actual needs to meet different scenarios. The design has a high degree of freedom. The structure can be customized as needed. The size, shape and arrangement of the periodic unit can be flexibly set. The materials can also be selected and combined as needed to meet the absorption band range.

[0021] In the wave absorption control step, the control accuracy of the intensity and direction of the magnetic field can be further improved to achieve more precise electromagnetic wave absorption control.

[0022] The present invention also provides the application of the tunable wave-absorbing metamaterial in the field of aerospace or communication equipment.

[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention effectively overcomes the shortcomings of the prior art in electromagnetic wave absorption and regulation by preparing a magnetic slurry with excellent performance and designing a specific preparation process. The tunable absorbing metamaterial in the present invention can achieve flexible, precise and stepless regulation of electromagnetic wave absorption, and the preparation process is simple and efficient, with relatively low cost, and has broad application prospects and practical value.

[0024] (2) The method of the present invention can achieve high-precision and efficient molding of complex metamaterial structures, avoiding the drawbacks of traditional processes. The absorbent material can accurately determine the absorption range and its composite use can widen the frequency band. The magnetic deformation characteristics of the tunable absorbing metamaterial can quickly and accurately adjust the absorbing frequency band under the action of the magnetic field, which is far superior to the fixed structure absorbing material. The pore structure design of the tunable absorbing metamaterial makes it extremely sensitive to deformation. A slight deformation can significantly change the absorbing performance. Combined with high-quality magnetic materials, it responds quickly to the magnetic field and can dynamically adapt to complex electromagnetic environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the design diagram of the rectangular cell structure in Example 1.

[0026] Figure 2 This is the magnetic domain distribution diagram of the rectangular cell structure in Example 1.

[0027] Figure 3 This is a microscopic morphology of the wire during the printing process of Example 1.

[0028] Figure 4 It is the sensitivity of the storage modulus and loss modulus of the magnetic slurry in Example 1 to the change of magnetic field.

[0029] Figure 5 This is a deformation sensitivity characteristic curve of the tunable absorbing metamaterial in Example 1 under the action of a 1 Hz frequency pulse electromagnetic field.

[0030] Figure 6 This is a diagram showing the tunable absorbing metamaterial's absorbing effect in Example 1.

[0031] Figure 7 This is a diagram showing the tunable absorbing metamaterial's absorbing effect in Example 2. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with the examples and drawings. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. Contents not described in detail in this specification belong to prior art known to professionals and technicians in the field.

[0033] In the printing process of the following embodiments, a slurry direct writing 3D printing device is used for 3D direct writing printing. The slurry direct writing 3D printing device includes a nozzle, a magnetic shielding sleeve is installed around the nozzle, and electromagnets are symmetrically arranged on the magnetic shielding sleeve around the nozzle. The direction of the magnetic field at the nozzle is changed by changing the current direction of the electromagnet, so that the extruded slurry is printed in a magnetic programming manner. After printing and forming, a thermal curing process is performed to realize the curing forming of the product's absorbing metamaterial.

[0034] Example 1 (1) First, NdFeB powder (average particle size not greater than 5 μm) was placed in anhydrous ethanol and ball-milled at 200 rpm for 7 hours. Then, it was transferred to a drying oven at 60°C for 24 hours, and ground carefully with a mortar, and then passed through a 200-mesh sieve to obtain unagglomerated NdFeB powder.

[0035] (2) The platinum silica gel matrix and the platinum catalyst (Ecoflex 00-30 Part B and Ecoflex 00-30 Part A, respectively) were mixed in a mass percentage of 1:1 and dispersed at a speed of 1500 rpm for 60 seconds using a planetary stirrer. Then, the reduced graphene oxide was added and dispersed at a speed of 2000 rpm for 120 seconds using a planetary stirrer. Then, the NdFeB powder obtained in step (1) was added and dispersed at a speed of 1500 rpm for 120 seconds using a planetary stirrer to prepare an unmagnetized printing slurry; in the slurry, the mass ratio of the platinum silica gel matrix, the reduced graphene oxide and the NdFeB powder was 20:1:29.

[0036] (3) placing the slurry from step (2) inside a permanent magnet for saturation magnetization treatment (about 3 T), thereby obtaining a magnetic slurry to be printed; (4) Use 3D modeling software to conduct the following research on the target absorbing metamaterial: Figure 1 The structural design of the rectangular cell is shown in Figure 1, and the planning is as follows: Figure 2 The distribution and orientation of the magnetic domains in the structure shown are converted into a format that can be recognized by the direct-write 3D printing device, and printed in the subsequent steps according to the above-designed method.

[0037] (5) The material tube containing the magnetic slurry in step (3) is accurately installed on the direct writing 3D printing device. A 20 mT annular permanent magnet is sleeved on the printing nozzle to align the magnetic domains during the printing process. During the printing process, a 410 μm nozzle is used, the printing speed is set to 6 mm / s, the single layer thickness is 0.35 mm, the printing height is 1.8 mm, and the printing is performed according to the method designed in step (4). The microscopic morphology of the printed wire is shown in the figure below. Figure 3 As shown in the figure, due to the weak extrusion swelling effect of the printing slurry, the magnetic domains are well ordered. The material obtained by the direct writing 3D printing device was placed in a drying oven at 210°C for 1 hour for thermal curing, and finally a tunable absorbing metamaterial with a pore structure that can be transformed under the drive of a magnetic field was prepared.

[0038] Based on the magnetic domain arrangement of the pore structure, the present invention successfully printed Figure 1 This superstructure has excellent negative expansion characteristics, and its pores can respond quickly to the magnetic field and produce different degrees of contraction.

[0039] In this embodiment, the magnetic slurry is subjected to a changing oscillating stress. Under these conditions, the storage modulus G' and loss modulus G'' Sensitivity to changes in magnetic field Figure 4 As shown, G' , G'' -The shear stress curve can better reflect the printability of the slurry. G' (Storage modulus)> G'' (loss modulus), indicating that the slurry is in a solid state, G' , G'' It decreases with the increase of shear stress. When the shear stress is about 82 Pa, G' (Storage modulus)< G'' (loss modulus), at this time the slurry turns into a liquid state, which fully demonstrates that this slurry has the characteristic of shear thinning. This shows that when using this slurry for printing, as the pressure inside the barrel increases, once it exceeds a certain pressure value, the slurry can be squeezed out of the needle. When the slurry is squeezed out of the needle, the shear pressure disappears instantly, and the elastic modulus returns to G'>G'' , the slurry returns to a solid state and can maintain the filament shape after extrusion.

[0040] Figure 5 The figure shows the deformation sensitivity characteristic curve of the tunable absorbing metamaterial under the action of a 1 Hz frequency pulse electromagnetic field. It is observed that due to its own inertia effect, the deformation rate of the absorbing metamaterial exceeds the speed of the dynamic magnetic field change, indicating that the control sensitivity can reach the second level.

[0041] The tunable absorbing metamaterial prepared in this embodiment has an absorbing effect without deformation. Figure 6 As shown, it can be found that the absorption efficiency reaches –32.11 dB in a specific frequency band, and the absorbing frequency can be adjusted around.

[0042] The statistical results of the absorbing performance of the tunable absorbing metamaterial under different magnetic fields are shown in Table 1. It can be seen that the absorbing performance of the tunable absorbing metamaterial is flexible and variable, and the absorbing frequency and absorption rate can be precisely controlled with the help of the magnetic field according to actual needs.

[0043] Table 1 Statistical results of the absorbing performance of tunable absorbing metamaterials under different magnetic fields

[0044] Example 2 (1) First, NdFeB powder (average particle size not greater than 5 μm) was placed in anhydrous ethanol and ball-milled at 250 rpm for 6 h. Then, it was transferred to a drying oven and dried at 70 °C for 22 h. It was ground with a mortar and then passed through a 250-mesh sieve to obtain unagglomerated NdFeB powder.

[0045] (2) A platinum silica gel matrix and a platinum catalyst (Ecoflex 00-30 Part B and Ecoflex 00-30 Part A, respectively) were mixed in a mass percentage of 1:1, and dispersed using a planetary stirrer at a speed of 1600 rpm for 50 s. Then, reduced graphene oxide was added and dispersed using a planetary stirrer at a speed of 2100 rpm for 110 s. The neodymium iron boron powder obtained in step (1) was added and dispersed using a planetary stirrer at a speed of 1600 rpm for 110 s to prepare an unmagnetized printing slurry. In the slurry, the mass ratio of the platinum silica gel matrix, reduced graphene oxide and neodymium iron boron powder was 20:1:26.

[0046] (3) placing the slurry from step (2) inside a permanent magnet for saturation magnetization treatment (about 2.7 T), thereby obtaining a magnetic slurry to be printed; (4) Use 3D modeling software to carry out the structural design of the triangular cell for the target absorbing metamaterial, and plan the distribution and direction of the magnetic domains in the triangular cell structure, convert it into a format that can be recognized by the direct writing 3D printing equipment, and print it according to the above designed method in the subsequent steps.

[0047] (5) The material tube containing the magnetic slurry in step (3) is accurately installed on the direct writing 3D printing device. The 25 mT annular permanent magnet sleeved at the printing nozzle is used to align the magnetic domains during printing. During the printing process, a 400 μm nozzle is used, the printing speed is 7 mm / s, and the single layer thickness is 0.25 mm and the height is 2.5 mm; printing is performed according to the method designed in step (4). The material obtained by the direct writing 3D printing device is placed in a drying oven at 220°C for thermal curing for 0.8 hours, and finally a tunable absorbing metamaterial whose pore structure can be transformed under magnetic field drive is prepared.

[0048] The tunable absorbing metamaterial prepared in this embodiment has an absorbing effect without deformation. Figure 7 As shown, it can be found that the absorption efficiency reaches –22.79 dB in a specific frequency band, and the absorption frequency can be adjusted around.

[0049] Example 3 (1) Al-Ni-Co alloy powder (average particle size not greater than 6 μm) was placed in anhydrous ethanol and ball-milled at 230 rpm for 7.5 hours. The powder was then transferred to a drying oven and dried at 62°C for 25 hours. The powder was ground in a mortar and passed through a 230-mesh sieve to obtain an unagglomerated Al-Ni-Co alloy powder.

[0050] (2) The polycarbonate matrix and the co-catalyst (benzoyl peroxide) were mixed at a mass ratio of 3:1, and dispersed for 180 seconds using a planetary ball mill (revolution 200 rpm, rotation 300 rpm), and then manganese zinc ferrite was added and dispersed for another 140 seconds. Then, the treated aluminum nickel cobalt alloy powder was added and dispersed for another 140 seconds to prepare an unmagnetized printing slurry, in which the mass ratio of the polycarbonate matrix, manganese zinc ferrite and aluminum nickel cobalt alloy powder was 28:1:36.

[0051] (3) placing the slurry from step (2) inside a permanent magnet for saturation magnetization treatment (about 2.9 T), thereby obtaining a magnetic slurry to be printed; (4) Use 3D modeling software to carry out structural design of pentagonal cells for the target absorbing metamaterial, plan the distribution and direction of magnetic domains in the pentagonal cell structure, convert it into a format that can be recognized by the direct writing 3D printing equipment, and print it according to the above designed method in the subsequent steps.

[0052] (5) The material tube containing the magnetic slurry in step (3) is accurately installed on the direct writing 3D printing device. The 20 mT annular permanent magnet sleeved at the printing nozzle is used to align the magnetic domains during printing. During the printing process, a 350 μm nozzle is used, the printing speed is 7 mm / s, the single layer thickness is 0.32 mm and the printing height is 1.9 mm; printing is performed according to the method designed in step (4). The material obtained by the direct writing 3D printing device is placed in a drying oven at 160°C for thermal curing for 1.1 hours, and finally a tunable absorbing metamaterial whose pore structure can be transformed under magnetic field drive is prepared.

[0053] Example 4 (1) SmCo alloy powder (average particle size not greater than 7 μm) was placed in anhydrous ethanol and ball-milled at 210 rpm for 6.8 hours. The powder was then transferred to a drying oven and dried at 58°C for 24.5 hours. The powder was ground in a mortar and passed through a 210-mesh sieve to obtain unagglomerated SmCo alloy powder.

[0054] (2) The polypropylene matrix and the co-catalyst (dibenzoyl peroxide) were mixed at a mass percentage of 2.5:1, and dispersed using a high-speed emulsifier at a rotation speed of 1400 rpm for 68 seconds. Subsequently, nickel-zinc ferrite was added and dispersed using a high-speed emulsifier at a rotation speed of 1700 rpm for 135 seconds. Finally, the treated samarium-cobalt alloy powder was added and dispersed using a high-speed emulsifier at a rotation speed of 1400 rpm for 135 seconds to prepare an unmagnetized printing slurry. In the slurry, the mass ratio of the polypropylene matrix, nickel-zinc ferrite and samarium-cobalt alloy powder was 25:1:30.

[0055] (3) placing the slurry from step (2) inside a permanent magnet for saturation magnetization treatment (about 3 T), thereby obtaining a magnetic slurry to be printed; (4) Use 3D modeling software to carry out the structural design of the circular cell for the target absorbing metamaterial, and plan the distribution and direction of the magnetic domains in the circular cell structure, convert it into a format that can be recognized by the direct writing 3D printing equipment, and print it according to the above designed method in the subsequent steps.

[0056] (5) The material tube containing the magnetic slurry in step (3) is accurately installed on the direct writing 3D printing device. The 23 mT annular permanent magnet sleeved at the printing nozzle is used to align the magnetic domains during printing. During the printing process, a 450 μm nozzle is used, the printing speed is 6.5 mm / s, the single layer thickness is 0.27 mm and the printing height is 2.1 mm; printing is performed according to the method designed in step (4). The material obtained by the direct writing 3D printing device is placed in a drying oven at 170°C for thermal curing for 1 hour, and finally a tunable absorbing metamaterial whose pore structure can be transformed under magnetic field drive is prepared.

[0057] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a tunable wave-absorbing metamaterial, characterized in that: The following steps are involved: (1) preparing a slurry comprising a polymer matrix, an absorber and magnetic particles, wherein the mass ratio of the polymer matrix, the absorber and the magnetic particles in the slurry is 20-30:1:20-40; and magnetizing the slurry to obtain a magnetic slurry; (2) Designing the porous target metamaterial structure to be printed, and performing magnetic programming design on the target metamaterial so that the pore structure transformation of the target metamaterial is adjustable under the action of a magnetic field; (3) placing the magnetic slurry of step (1) in a slurry direct writing 3D printing device, printing it according to the method designed in step (2), and thermally curing it after printing to prepare a tunable absorbing metamaterial whose pore structure can be transformed under the drive of a magnetic field.

2. The method for preparing a tunable absorbing metamaterial according to claim 1, characterized in that: The high molecular polymer matrix includes silicone rubber, polydimethylsiloxane, polyurethane, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polycarbonate, polyamide or polyester.

3. The method for preparing a tunable absorbing metamaterial according to claim 1, characterized in that: The wave absorbing agent is selected from at least one of reduced graphene oxide, carbon nanotubes, carbonyl iron powder, manganese zinc ferrite, nickel zinc ferrite, silver nanoparticles, gold nanoparticles, polyaniline, polypyrrole, silicon carbide, titanium dioxide, and hexagonal boron nitride.

4. The method for preparing a tunable absorbing metamaterial according to claim 1, characterized in that: The magnetic particles are hard magnetic particles, which include at least one of neodymium iron boron powder, samarium cobalt alloy powder, barium ferrite powder, strontium ferrite powder and aluminum nickel cobalt alloy powder; the particle size of the hard magnetic particles is ≤30 μm.

5. The method for preparing a tunable absorbing metamaterial according to claim 1, characterized in that: The slurry is magnetized to saturation under a pulse magnetic field or a permanent magnet to obtain a magnetic slurry.

6. The method for preparing a tunable absorbing metamaterial according to claim 1, characterized in that: The slurry direct writing 3D printing device includes a nozzle, a magnetic shielding sleeve is installed around the nozzle, and electromagnets are symmetrically arranged on the magnetic shielding sleeve around the nozzle. The direction of the magnetic field at the nozzle is changed by changing the current direction of the electromagnet, so that the extruded slurry is printed in a magnetic programming manner.

7. The method for preparing the tunable absorbing metamaterial according to claim 6, characterized in that: During the printing process, the nozzle diameter is 210-620 μm, the printing speed is set to 3-15 mm / s, the thermal curing conditions are 20-250°C, and the time is 30min-10h.

8. A tunable microwave-absorbing metamaterial prepared according to the method for preparing a tunable microwave-absorbing metamaterial according to any one of claims 1 to 7.

9. The tunable absorbing metamaterial according to claim 8, characterized in that: The tunable wave-absorbing metamaterial has a pore structure that exhibits different degrees of contraction as the intensity of the magnetic field changes.

10. Application of the tunable wave-absorbing metamaterial according to claim 9 in the field of aerospace or communication equipment.

Citation Information

Patent Citations

  • Dual-band tunable broadband wave-absorbing structure based on resistive film periodic structure

    CN117335167A

  • Wave-absorbing structure, device and preparation method thereof

    CN111786128A

  • Preparation method of magnetic control tunable wave-absorbing plate based on 3D printing

    CN113969046A

  • Flexible and elastic wave-absorbing metamaterial as well as preparation method and application thereof

    CN116053802A

  • Preparation method of square pattern magnetic control tunable electromagnetic wave absorber

    CN116728816A

Cited By

  • A reconfigurable metamaterial interlayer hybrid structure based on PIN diodes and its fabrication method

    CN122576699A